2015
DOI: 10.2298/vsp1506505v
|View full text |Cite
|
Sign up to set email alerts
|

Association between risk factors, basal viral load, virus genotype and the degree of liver fibrosis with the response to the therapy in patients with chronic hepatitis C virus infection

Abstract: The results of our study showed that the treatment outcome of chronic HCV infection was associated with baseline HCV ribonucleic acid, HCV genotype, route of infection and the degree of histopathological changes in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In alignment with other published studies [ 30 , 44 ] our research didn’t find association between cholesterol levels, insulin levels and HOMA-IR with antiviral response this may be probably explained by the absence of diabetes among our patients. On the other hand it was found that baseline lower viral load is a direct predictor to SVR rates as proved previously [ 45 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In alignment with other published studies [ 30 , 44 ] our research didn’t find association between cholesterol levels, insulin levels and HOMA-IR with antiviral response this may be probably explained by the absence of diabetes among our patients. On the other hand it was found that baseline lower viral load is a direct predictor to SVR rates as proved previously [ 45 ].…”
Section: Discussionsupporting
confidence: 78%
“…Yet increased the probability of SVR in IL28B C/T + T/T from 27 % to reach 50 %. Advanced fibrosis was proven previously to be a main factor for Peg-IFN and RBV treatment failure [ 45 ]. Thus more practically our study interestingly found that only serum levels of 25-OH vitamin D, VDR rs2228570 A/A genotype together with IL28B rs12979860 C/C genotype were the only predictors of SVR in none-F4 CHC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, gender, age, basal viral load, HCV genotype, histopathology and risk factors for acquiring HCV infection were not associated with therapy response (p>0,05). These discrepancies may be related to the size of the study group, as our previously published data with a larger group of 121 patients showed that treatment outcome was associated with baseline HCV RNA, HCV genotype, infection route and the degree of histopathological liver changes (14).…”
Section: Discussionmentioning
confidence: 90%
“…Two of the most important concepts in current practice are those of wound bed preparation and control of bacterial burden since wound healing is a dynamic process involving several phases, including hemostasis, inflammation, migration, proliferation, and maturation . Would healing requires a moist environment while simultaneously preventing infections that may complicate and prolong the healing process . In clinical settings, antibacterial agents are used in high doses to prevent infection, lead to low biosafety.…”
Section: Discussionmentioning
confidence: 99%